Fluoxetine Protection in Decompression Sickness in Mice is Enhanced by Blocking TREK-1 Potassium Channel with the “spadin” Antidepressant - Vallée, Nicolas; Lambrechts, Kate; De Maistre, Sébastien; Royal, Perrine; Mazella, Jean; Borsotto, Marc; Heurteaux, Catherine; Abraini, Jacques; Risso, Jean-Jacques; Blatteau, Jean-Eric (Frontiers in Physiology, 2016)
In mice, disseminated coagulation, inflammation and ischemia induce neurological damages that can lead to the death. These symptoms result from circulating bubbles generated by a pathogenic decompression. An acute fluoxetine treatment or the presence of the TREK-1 potassium channel increased the survival rate when mice are subjected to an experimental dive/decompression protocol. This is a paradox because fluoxetine is a blocker of TREK-1 channels. First, we studied the effects of an acute dose of fluoxetine (50mg/kg) in wild-type (WT) and TREK-1 deficient mice (Knockout homozygous KO and heterozygous HET). Then, we combined the same fluoxetine treatment with a five-day treatment by spadin, in order to specifically block TREK-1 activity (KO-like mice). KO and KO-like mice could be regarded as antidepressed models. 167 mice (45 WTcont 46 WTflux 30 HETflux and 46 KOflux) constituting the flux-pool and 113 supplementary mice (27 KO-like 24 WTflux2 24 KO-likeflux 21 WTcont2 17 WTno dive) constituting the spad-pool were included in this study. Only 7% of KO-TREK-1 treated with fluoxetine (KOflux) and 4% of mice treated with both spadin and fluoxetine (KO-likeflux) died from decompression sickness (DCS) symptoms. These values are much lower than those of WT control (62%) or KO-like mice (41%). After the decompression protocol, mice showed a significant consumption of their circulating platelets and leukocytes. Spadin antidepressed mice were more likely to declare DCS. Nevertheless, which had both blocked TREK-1 channel and were treated with fluoxetine were better protected against DCS. We conclude that the protective effect of such an acute dose of fluoxetine is enhanced when TREK-1 is inhibited. We confirmed that antidepressed models may have worse DCS outcomes, but a concomitant fluoxetine treatment not only decreases DCS severity but increases the survival rate.